A new species of Salix (Salicaceae) from Michoacán, Mexico - Carranza Gonzalez, Eleazar (Instituto de Ecología, A.C., 1995)
Salix aeruginosa is described as a new species from the state of Michoacán. It is found on Northern slopes of the Transversal Volcanic Belt, in wet ravines with both oak forest and oak-pine forest. This plant is closely related to S. jaliscana Jones, however, it differs in the shape of leaves, stipules and fruits.